Associations between sleep deficit and academic achievement - triangulation across time and subject domains among students and teachers in TIMSS in Norway - Vik, Frøydis N.; Nilsen, Trude; Øverby, Nina C. (BMC public health, 2022)
Sufficient sleep is important to an individual's health and well-being, but also for school achievement among adolescents. This study investigates the associations between sleepiness, sleep deficits, and school achievements among adolescents. This trend study involved a representative sample of Norwegian adolescents based on the "Trends in International Mathematics and Science Study" (TIMSS), N = 4499 (2015) and N = 4685 (2019) and their teachers. The students were 9th graders from a Norwegian compulsory secondary school. The survey included questions on students' sleepiness as students reported in 2019 and sleep deficits among students that limited teaching in class as their teachers reported in 2015 and 2019. Regression, triangulation, and mediation analyses were used. Mplus was used to perform the statistical analyses. The results revealed significant negative associations between sleep deficits and school achievements, adjusted for gender, socioeconomic status (SES), and minority status among Norwegian 9th graders. These results were found for both mathematics and science achievements in 2015 and 2019. Sleepiness that the students reported was negatively associated with school achievements in 2019. Trend and mediation analyses showed that sleep deficits explained 18 and 11% of the decrease in mathematics and science achievements, respectively, from 2015 to 2019. Sleep deficits were associated with school achievements in mathematics and science among Norwegian 9th graders. Mediation analyses revealed that sleep deficits explained a significant part of the decline in academic achievements. Insufficient sleep may have negative public health implications and influence adolescents' academic achievements and competences, and should therefore be discussed in both the educational and health systems.